Islamic Legal Paradigm and Methodology Philosophy and Sufi Interpretation - U. Abdurrahman; Moh Najib; Ayi Sofyan (Westscience Press, 2023)
The Qur'an, as a miracle of the Prophet Muhammad, has been proven to be able to reveal its extraordinary miraculous side, not only in its existence which has never been fragile, but also in its teachings which have been proven to be in accordance with the times. The Qur'an not only talks about morality and spirituality, but also talks about science related to human life. Many tafsir scholars have written several works on methods of interpreting the Qur'an. From these scholars emerged various models and methods of interpretation in order to reveal the messages of the Qur'an optimally according to their abilities and abilities. their social conditions. In this article, the author will try to describe two exegetical methodologies, namely philosophical exegesis and Sufi exegesis.